Estimating the choice of entrepreneurship as a career: The case of Universiti Utara Malaysia - Mohamad, Noorkartina; Lim, Hock Eam; Yusof, Norhafezah; Kassim, Mustafa; Abdullah, Hussin (Universiti Malaysia Sarawak, 2014)
Using of the case of Universiti Utara Malaysia (UUM), this study aims to estimate the factors that influence the entrepreneurship career choice among UUM students and graduates, in particular, the effect of educational factor on the probability that a graduate will choose entrepreneurship as his or her career.Results of descriptive statistics reveal that the tendency of choosing entrepreneurship as career is high among the sample and it is associated with gender, ethnic groups, degree, CGPA and family entrepreneurship experiences.Nevertheless, the estimated Multinomial Logit model indicates that the significant factors are entrepreneur education, family entrepreneurship experiences and economic factor (proxy by intention to start a business upon graduation).The significant of educational factor implies that the educated entrepreneur can be cultivated and this empirical result supports the current policy of Malaysia government to grow the graduate entrepreneur through education.The findings of this paper suggest that entrepreneurship should be viewed as an important career choice among the university students and graduates.This career choice is seen as a choice that could improve the economy performance, particularly to the labor market because the entrepreneurship activity is able to create more jobs and prosperous.